Tinjauan Maslahah Mursalah terhadap Pembatalan Peraturan Menteri Ketenagakerjaan Nomor 2 Tahun 2022 tentang Jaminan Hari Tua (JHT) - Mitsaq Gholidh Al Rasyid; Eva Fauziah (UNISBA Press, 2023)
Abstract. The government's policy regarding Old Age Guarantee (JHT) has undergone several changes. The second change drew a wave of protests from various elements of society and workers. The wave of protests has affected the government's policy in determining the timing of disbursement of JHT benefit funds and changing with the new Permenaker Number 4 of 2022. This study aims to examine the factors of changes in permenaker policy Number 2 of 2022 through maslahah mursalah. This research method uses normative juridical methods with data collection techniques through literature studies in the form of books, journals, and documents related to the problem under study. The results of this study show that government policies related to JHT have changed, the factors for the advent of Permenaker No.2 of 2022 are government considerations that consider that there are no rules that guarantee workers who are laid off and there is a development of social security protection, a mandate from Government Regulation Number 60 of 2015 concerning the Implementation of the JHT Old Age Guarantee Program. Maslahah Mursalah's analysis of government policies related to the cancellation of Permenaker Number 2 of 2022 concerning Procedures and Requirements for Payment of Old Age Guarantee Benefits (JHT) including to maslahat al-'ammah (benefits that concern the interests of many people). Abstrak. Kebijakan pemerintah terkait Jaminan Hari Tua (JHT) telah mengalami beberapa perubahan. Perubahan kedua mengundang gelombang protes dari berbagai elemen masyarakat dan buruh. Gelombang protes tersebut telah memengaruhi kebijakan pemerintah dalam penentuan waktu pencairan dana manfaat JHT dan mengubah dengan Permenaker baru Nomor 4 Tahun 2022. Penelitian ini bertujuan untuk meneliti tentang faktor perubahan kebijakan Permenaker Nomor 2 Tahun 2022 melalui maslahah mursalah. Metode penelitian ini menggunakan metode yuridis normatif dengan teknik pengumpulan data melalui studi pustaka berupa buku-buku, jurnal, dan dokumen yang berkaitan dengan masalah yang diteliti. Hasil penelitian ini menunjukkan bahwa kebijakan pemerintah terkait JHT mengalami perubahan, faktor-faktor lahirnya Permenaker No.2 Tahun 2022 adalah adanya pertimbangan pemerintah yang menganggap belum ada aturan yang menjamin para pekerja yang terkena PHK dan adanya perkembangan perlindungan jaminan sosial, amanat dari Peraturan Pemerintah Nomor 60 Tahun 2015 tentang Penyelenggaraan Program Jaminan Hari Tua JHT). Analisis Maslahah Mursalah terhadap kebijakan pemerintah terkait pembatalan Permenaker Nomor 2 Tahun 2022 tentang Tata Cara dan Persyaratan Pembayaran Manfaat Jaminan Hari Tua (JHT) termasuk kepada maslahat al-‘ammah (kemaslahatan yang menyangkut kepentingan orang banyak).